Analysing literacy and other psychological tendencies using linguistic profile in English expressive writing: Are students able but unwilling to write? - Lee, Bonita; Fitria, Annisa; Ginting, Henndy (Indonesian Journal of Applied Linguistics, 2019)
The use of English in educational settings has become quite common in order to achieve global competitiveness. Given this fact, students are required to be fluent both in oral and written English. Unfortunately, the significant discrepancy is often found between the two. Students seemed to struggle when asked to elaborate their ideas in writing. With that in mind, this study would elaborate on the linguistic properties of students’ writings in order to understand the linguistic processes affecting such a discrepancy. Writings from a total of 205-business students were analysed using Linguistic Inquiry Word Count (LIWC2015) focusing on the linguistic and grammatical properties such as word counts, tenses associated words, adjectives, adverbs and so on. We found that our samples’ writing profile was significantly different from those of LIWC2015, especially in properties such word counts, six-letter words, verb and adjectives, as well as the use of I-related pronoun. For example, we found that our sample used a lot more difficult words while wrote less than half of the global population, suggesting their ability as well as unwillingness to write at the same time. With this main finding, we concluded that students come short in terms of critical literacy. In addition to that, we would also discuss the potential psychological implications (narcissistic tendency) as well as the differences between men and women styles in writing.